A critical interpretive synthesis of informal payments in maternal health care. Issue 3 (21st March 2019) - Schaaf, Marta; Topp, Stephanie M
Abstract: Informal payments for healthcare are widely acknowledged as undercutting health care access, but empirical research is somewhat limited. This article is a critical interpretive synthesis that summarizes the evidence base on the drivers and impact of informal payments in maternal health care and critically interrogates the paradigms that are used to describe informal payments. Studies and conceptual articles identified both proximate and systems drivers of informal payments. These include norms of gift giving, health workforce scarcity, inadequate health systems financing, the extent of formal user fees, structural adjustment and the marketization of health care, and patient willingness to pay for better care. Similarly, there are proximal and distal impacts, including on household finances, patient satisfaction and provider morale. Informal payments have been studied and addressed from a variety of different perspectives, including anti-corruption, ethnographic and other in-depth qualitative approaches and econometric modelling. Summarizing and discussing the advantages and disadvantages of these and other paradigms illustrates the value of an inter-disciplinary approach. The same tacit, hidden attributes that make informal payments hard to measure also make them hard to discuss and address. A multidisciplinary health systems approach that leverages and integrates positivist, interpretivist and constructivist tools of social science research can lead to better insight. With this, we can challenge 'master narratives' and meet universalistic, equity-oriented global health objectives.